Advances and prospects of biochar in improving soil fertility, biochemical quality, and environmental applications - Nepal, Jaya; Ahmad, Wiqar; Munsif, Fazal; Khan, Aziz; Zou, Zhiyou (Frontiers in Environmental Science, 2023)
With the global food deficit increasing and rising climate change issues, there is a need to find green solutions to improve soil fertility and productivity while enhancing soil biochemical quality and reducing the ecological impact of agriculture. Biochar is a potentially cost-effective, carbonaceous resource with many agricultural and environmental applications. As a soil amendment, it improves soil physical and biochemical properties and increases soil fertility and productivity—particularly over the long-term—increasing soil aggregation, water retention, pH, and microbial activities, thus, improving overall soil quality, potentially helping to reduce chemical fertilizer needs over time. The extent of biochar's impact on soil physiochemical properties varies depending on biochar source, type, size, inherent soil characteristics, cropping system, etc. Moreover, biochar has significant potential in soil and water remediation, especially through its unique adsorption and chemical properties capable to capture and immobilize pollutants such as metal(loid)s, organic pollutants, and hazardous emerging contaminants such as microplastics. Further, biochar has also emerged as a key strategic, cost-effective material to tackle global issues such as climate change mitigation, reducing the net greenhouse gas emission to minimize global warming potential. However, a knowledge gap remains as to understanding the long-term persistence of biochar on agroecosystem, optimal biochar application rate for the diversity of biochar-soil-crop-environmental conditions, interaction of biochar with inherent soil carbon stock, specific mechanisms of biochar’s effect on soil biotic properties, quantification of carbon sequestration, greenhouse gas emissions, synergy or potential antagonistic effects with other carbon sources such as compost, manure, residues, etc., its modification for environmental applications and associated environmental and human risks over long-term. Further research is needed to evaluate the long-term impacts of types and sizes of biochar on overall soil quality to recommend suitable application practices based on soil management and cropping system. Also, its environmental applications need to be fine tuned for wider and target specific applications to tackle pressing environmental issues such as soil and water pollution.